CAUSAL RELATIONSHIP MODEL OF FACTORS AFFECTING THE REPURCHASE OF CAR HIRE PURCHASE SERVICE OF THE CUSTOMERS AT ASIA SERMKIJ LEASING PUBLIC COMPANY LIMITED - Thatsana-ekchit, Chaipat; Ampavat, Kreagrit (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This research aims 1) to study the level of comments on Service Marketing Mix, Psychological Factors, Service Quality, Decision to Use Car Hire Purchase and Repurchase 2) to study influence of Service Marketing Mix, Psychological Factors, Service Quality on the Decision to Use Car Hire Purchase 3) to study influence of Decision to Use Car Hire Purchase on the Repurchase. The samples are 400 customers who have used the service at Asia Sermkij Leasing Public Company. A questionnaire is used as instrument to collect data with a 5 points scale. Data is analyzed by using the structural equation modeling (SEM). The results showed that: 1) the level of Service Marketing Mix, Psychological Factors, Service Quality, Decision to Use Car Hire Purchase and Repurchase are high level. Moreover. 2) Service Marketing Mix has no influence on Decision to Use Car Hire Purchase. However, Psychological Factors and Service Quality have a positive influence on Decision to Use Car Hire Purchase. Furthermore. 3) Decision to Use Car Hire Purchase has a positive influence on Repurchase.